Standardizing the recipes mainly used in the menus of commercially operating institutional food services: their nutritional values and cost analysis - Dağ, Ayhan; Merdol, Türkan Kutluay (Progress in Nutrition, 2020)
Objective: This research was carried out at Bilkent University cafeterias to standardize the recipes that are not available for specific dishes which are mainly used by commercially operating mass feeding institutions. Throughout the study, 75 food recipes classified under 9 categories (soups, meat, chicken, fish, vegetables cooked with meat, cold vegetable dishes cooked with olive oil, pastries, salads and desserts) were standardized for 100 portions and written to the forms redeveloped by the researchers. All of the dishes were prepared, cooked and served by the cooks working at Bilkent University main kitchen. Recipe base line information was created by combining the data collected both from the well experienced cooks and famous cook books. The organoleptic evaluation of the recipes to be standardized were made by using a 5 points scale evaluation form which was based on 5 criteria (colour-shape, general appearance, flavour-taste, textureconsistency, portion size) and graded by the panellists composed of dietitians, university students, university staff and cooks. Fifty nine of these recipes were standardized following their initial, 9 after their second, and 7 after their third trial of production. The recipes which were perceived to be average and/or below by the panellists were produced again considering their shortcomings until the desired points were achieved. Energy and nutrient content of the recipes were calculated using BEBİS (computerized program giving the energy and nutrient values of given food and recipes that are specific for Turkish dishes) program. The cost of the recipes was calculated as food cost and the total cost. The food cost was calculated by the ingredients’ cost indexed to the value of American Dollar is due to its consistent rate compared to Turkish Liras. Total cost was achieved by the factors affecting the cost of the dish such as the cost of employee and other technical costs. Total cost was calculated to determine the sale price of the dishes. Energy and nutrient content and the total cost of the dishes were shown on the standardized recipe forms. It was found that the percentages of the food, labour and the operational cost of the total cost were 33.3 %, 29.9 % and 26.4% of the total cost respectively.